Selection Practices and Customer Relationship Activities Mediated by Cultural Ideologies: An Empirical Study with Malaysian Organisations - Liu, Yi; Pearson, Cecil; Chatterjee, Samir (Maxwell Science Publications, 2014)
Generating competiveness is an urgent priority for corporate global economic advancement, which is promoting attention to acquiring, developing and retaining a new type of internationally linked personnel. The importance of global mindset and related competencies has yet to receive wider scholarly attention in most Asian economies and this study addresses that gap by providing an exploratory empirical investigation of 132 Malaysian managers. Findings from an analysis of primary data demonstrate selection procedures play an important role in facilitating the customer relationship activities on synergistic business operations and these connections are culturally impacted. These exploratory observations infer business style and structures are shaped by cultural forces to provide a departure point for future investigations.